Processo de morte e morrer: desafios no cuidado de enfermagem ao paciente e família - Maria Eduarda Grams Salum; Carolina Kahl; Kamylla Santos da Cunha; Cintia Koerich; Thiago Oliveira dos Santos; Alacoque Lorenzini Erdmann (Universidade Federal do Ceará, 2017)
Objective: to understand the actions and interactions performed by nurses in caring for patients and their family in the process of death and dying. Methods: a qualitative study implementing a theoretical and methodological contribution of Grounded Theory. An individual interview was conducted with 18 participants, divided into three sample groups. Results: weakness in nurses' training regarding the death-dying process, the importance of the nurse-patient bond, family members support, and respect for the grieving process is apparent. As coping strategies, ongoing education, sharing experiences with peers and attachment to spiritual beliefs can be emphasized. Empathy appears as the main challenge, considering the influence of personal and bureaucratic factors. Conclusion: the way nurses respond to the challenges of their professional performance, seeking to build a bond with patients and families, supporting and respecting their process of mourning based on empathy stand out among the actions and interactions performed in care of the patient and family in the process of death and dying.